The effects of single leg stance during daily toothbrushing on the balance skills of elderly adults - Ebubekir Aksay (IP Iermakov S.S., 2021)
Background and Study Aim. It was aimed to measure the effects of single-leg stance on measuring the individual postural limits and balance skills of elderly adults. Material and Methods. The present study involved a total of 360 elderly adults aged between 70 and 80 years. The participants were divided into two groups as 187 individuals in experiment group (99 women / 88 men) and 173 individuals in control (94 women / 79 men). In measuring the risk of fall and balance skills, the Functional Reach Test, Timed up and go Test, and Single Leg Stance Test were used. The participants in experiment group were asked to stand on one foot for a total of 4 minutes (2 minutes in morning and 2 minutes in evening) every day while brushing their teeth for 50 weeks. Since the data showed normal distribution, the independent samples t-test was used in determining the intergroup difference, whereas the dependent sample t-test was used in determining the intragroup pretest-posttest difference. Results. It was determined that there was a significant relationship between elderly adults' balance skills and 4-min/day single-leg stance practice (p<0.05). In all the tests, it was found that the balance skills of women and men have improved and men had better values in comparison to women. Conclusion. It is thought that, via simple procedures such as lifting up one foot while brushing the teeth, the balance skills of elderly adults can be improved, the risk of fall can be reduced. They can be supported in terms of living an independent life.